The problem of Intellectual Lithuanian Literature: The Case of Ramūnas Klimas - Tutlytė, Kristina (Colloquia, 2021)
Using the approach of cognitive poetics, the author of the article analyses Ramūnas Klimas’ story, Gintė ir jos žmogus [Gintė and Her Man]. By employing Peter Stockwell’s concept of cognitive deixis, the technique of deictic transfer and aspects of schema theory in the text, the fundamental mechanisms of the construction of the story have been highlighted, which in turn, lead to the observation that the text provokes the delayed categorization discussed by Reuven Tsur. In the text, the deictic center of the implicit reader is being developed in different temporal and spatial dimensions using deixis of the respective categories. The interpretation is complicated by the highlighting of the textual deixis: several versions of the same story are presented, the process of the narration itself is commented, and the reader is addressed directly, which, according to Stockwell, can be understood as an attempt to destroy the reader’s belief in the truthfulness of the story being told and to put them out. These formal features also determine the depth and multi-layered nature of the text. Looking at the formal elements of the text and the techniques it employs from the point of view of cognitive poetics, the story by Klimas can be viewed as an attempt to criticize the official Soviet discourse and undermine the dangers of trusting blindly the truth proclaimed by one man.